2016
DOI: 10.4037/ccn2016276
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Family Satisfaction With Care Delivered in the Intensive Care Unit

Abstract: Background In our competitive health care environment, measuring the experience of family members of patients in the intensive care unit to ensure that health care providers are meeting families’ needs is critical. Surveys from Press Ganey and the Centers for Medicare and Medicaid Services are unable to capture families’ satisfaction with care in this setting. Objective To implement a sustainable measure for family satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 23 publications
3
41
0
11
Order By: Relevance
“…Seven studies, four of which were large multicentre studies, investigated family satisfaction with care and decision‐making in the ICU. Three studies used quantitative methods (Heyland, Rocker, & Dodek, ; Hunziker et al, ; Hwang et al, ) and four were mixed methods studies (Clark, Milner, Beck, & Mason, ; Hendrich et al, ; Karlsson, Tisell, Engrstom, & Andershed, ; Schwarzkopf et al, ). No qualitative studies of family satisfaction with care in ICU were found (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven studies, four of which were large multicentre studies, investigated family satisfaction with care and decision‐making in the ICU. Three studies used quantitative methods (Heyland, Rocker, & Dodek, ; Hunziker et al, ; Hwang et al, ) and four were mixed methods studies (Clark, Milner, Beck, & Mason, ; Hendrich et al, ; Karlsson, Tisell, Engrstom, & Andershed, ; Schwarzkopf et al, ). No qualitative studies of family satisfaction with care in ICU were found (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Research study findings suggest that families of the critically ill are highly satisfied with the care their relative receives, especially with aspects of care about skill and competence of staff and the respect given to the patient (Clark et al, ; Hendrich et al, ; Heyland et al, ; Hunziker et al, ; Hwang et al, ; Schwarzkopf et al, ). Families were less satisfied with emotional support, the provision of understandable, consistent information and coordination of care (Clark et al, ; Hendrich et al, ; Heyland et al, ; Hunziker et al, ; Hwang et al, ; Schwarzkopf et al, ). Families felt more satisfied when clear, honest information was delivered to them in understandable language as this enables them to actively participate in the decision‐making process (Heyland et al, ; Hunziker et al, ; Hwang et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations